USE OF MISOPROSTOL FOR INDUCTION OF LABOUR IN UNFAVOURABLE CERVIX - Haider, Gulfareen; Nizam, Khairunnisa (Pakistan Armed Forces Medical Journal, 2011)
Objective: Objective of this study was to determine the maternal and fetal outcome after induction of labour with misoprostol in term pregnancies with unripened cervix. Study Design: Experimental study. Place and Duration of Study: Non probability convenient, in the labour ward of Nawabshah medical college hospital Sindh, Pakistan from 6th April 2008 to 5th Dec 2008. Material and Methods: Total 114 patients were induced with misoprostol who had singleton pregnancy of more than 36 weeks with cephalic presentation, reactive CTG and unfavorable cervix (Bishop Score <4). Sampling strategy was non probability convenient sampling. However, patients with previous cesarean section, parity >4, nonreactive CTG, any contraindication to induction of labour and bishop score > 4 were excluded from the study. After taking an informed consent, patients were given 100mcg misoprostol in posterior fornix of vagina every 6 hour till 3 doses or initiation of labour. Labour was recorded on partogram. Maternal and fetal outcome were recorded on a self designed proforma. Results: Majority of patients i.e. 63(55.2 6%) belonged to age group of 23-30 years. Eighty seven (76.31%) patients who received induction were primigravida while 27(23.68%) patients were P2-P4. Thirty six (31.57%) patients required single dose of misoprostol, 54(47.36%) patients required two doses while 24(21%) patients required three doses. Out of all these 114 patients, labour was successfully completed in 93(81.57%) patients. While cesarean section was done in 21(18.42%) patients. About 48(42.10%) patients were delivered in 8 to 9 hours. Uterine hyper stimulation was seen in 9(7.89%) patients. Apgar score was less than 7 in six (5.26%) newborns. Conclusion: Misoprostol is safe for induction of labour with an unfavorable cervix. The results were satisfying with minimal complications.